Factors associated with the scientific production indexed in Scopus of a Universidad Nacional Mayor de San Marcos - Vílchez-Román, Carlos (2019)
One of the challenges faced by research managers is to identify the factors associated with the scientific production of a university, because in this they can allocate resources to expand the frontiers of academic knowledge. In this study we present a model of factors associated with the scientific production indexed in Scopus of a Peruvian public university. For the data modeling, a longitudinal design based on time-series analysis was used, considering lags from one to ten years. Initially (lag = 1 year), the number of international partners and graduated doctors were the two factors associated with scientific production indexed in Scopus, but when incorporating the temporal perspective (lag = 5 years), only the number of doctors remained as predictor, in a statistical sense, of the scientific production of the Peruvian public university analyzed in this investigation.